Gambaran Self Esteem Mahasiswa Psikologi Universitas X yang Mempunyai Orangtua Bercerai - Kinkie, Emmanuella Anastacia; Subroto, Untung (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Self-esteem is a form of self-recognition in assessing interpersonal relationships. It is also an important aspect for university students in building their confidence. Parental divorce can have an impact on students' self-esteem. This study aims to explore the self-esteem of psychology students at University X whose parents are divorced. The research adopts a qualitative method using interviews and observations, involving six student participants aged 18–24 years who experienced parental divorce within the past 1–5 years. Data were collected through in-depth interviews to uncover participants’ experiences, perspectives, and the effects of divorce on their self-esteem. The findings indicate that some participants exhibit high self-esteem, as reflected in their motivation to achieve academic goals and their ability to cope with the emotional effects of divorce. However, some participants were found to have low self-esteem, characterized by a lack of confidence and difficulties in social relationships.